The Performance of Undiversified Portfolio In Indonesia Stock Exchange - Budi Frensidy (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
This research is aimed to analyze the diversification practice among domestic retail investors at the Indonesia Stock Exchange (IDX) and its portfolio performance. An individual domestic investor at IDX holds 4.3 stocks on average with the median two stocks. This is in line with the findings of Goetzmann & Kumar (2008), Kelly (1995), and Polkovnichenko (2005). For the performance, without considering risk, minimum and moderate diversification portfolios tend to be better than the extensive diversification. However, when risk is taken into account, the undiversified portfolios do not outperform the extensive diversification.